KREATIVITAS MAHASISWA PADA HASIL PRODUK MATA KULIAH GASTRONOMI DI PRODI PEMDIDIKAN KESEJAHTERAAN KELUARGA JURUSAN KESEJAHTERAAN KELUARGA - Mandasari, Yulia; Elida, Elida; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
The purpose of research is describe the creativity of students in terms offood product design and product results subjects gastronomic in program of studyPendidikan Kesejahteraan Keluarga majors of kesejahteraan keluarga This studyis a descriptive kualitatif study. Object this study is creativity of students in termsof food product design and product results subjects gastronomic. Soource of datais college student which follows the subjects of gastronomy and the lecture. Datacollection techniques with observation, interview and documentation. analysistechniques with reduction data, display of data and conclusion. The resultsshowed that (1) lack of creativity of college student designing food products Thislooks the lack of innovation and improvisation in the food product designsimplicity, harmony, rhythm, indivisibility and balance (2) creativity collegestudent of product results on gastronomic subjects is the result of food productsmade some of implementation, the processing of products and the presentation ofthe results of the product. This looks the lack of innovation and improvisationresults of food products on the shape, color, texture and garnish .Keywords: Creativity, College Student Design and Product Results